Grammatical Gender in German Influences How Role-Nouns Are Interpreted: Evidence from ERPs. Issue 8 (17th November 2019) - Misersky, Julia; Majid, Asifa; Snijders, Tineke M.
ABSTRACT: Grammatically masculine role-nouns (e.g., Studenten masc.'students') can refer to men and women but may favor an interpretation where only men are considered the referent. If true, this has implications for a society aiming to achieve equal representation in the workplace since, for example, job adverts use such role descriptions. To investigate the interpretation of role-nouns, the present ERP study assessed grammatical gender processing in German. Twenty participants read sentences where a role-noun (masculine or feminine) introduced a group of people, followed by a congruent (masculine– men, feminine– women ) or incongruent (masculine– women, feminine– men ) continuation. Both for feminine- men and masculine- women continuations a P600 (500 to 800 ms) was observed; another positivity was already present from 300 to 500 ms for feminine- men continuations but critically not for masculine- women continuations. The results imply a male-biased rather than gender-neutral interpretation of the masculine—despite widespread usage of the masculine as a gender-neutral form—suggesting that masculine forms are inadequate for representing genders equally.